Eksplorasi Pelanggaran Etika Bisnis dan Dampaknya terhadap Kesejahteraan Psikologis Karyawan : Studi Kasus pada Industri Kreatif - Soffi Assifa Insani; Halimah Zahrah; Silva Novianti; Nida Windatun (Teewan Journal Solutions, 2025)
This article discusses violations of business ethics at Brandoville Studios, a Jakartabased animation and game development company. The case emerged after reports from former employees of exploitative work practices, verbal and physical abuse, and violations of basic workers' rights. This study aims to analyze the forms of ethical violations committed by the company and their impact on the work environment and basic principles of business ethics.This study uses a qualitative method with a descriptive approach. Data were obtained through analysis of documentation, media reports, and literature studies. The results of the study indicate that Brandoville Studios has violated the basic principles of business ethics, including fairness, integrity, social responsibility, and respect for human rights. These findings indicate that there are still serious challenges in implementing business ethics in the creative industry in Indonesia. Therefore, it is necessary to increase company awareness of the importance of work ethics and stricter supervision from the authorities to prevent exploitation in the workplace.